2016 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2016
DOI: 10.1109/cvpr.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

ReconNet: Non-Iterative Reconstruction of Images from Compressively Sensed Measurements

Abstract: Ground Truth 25% measurements 4% measurements 1% measurementsFigure 1: Given the block-wise compressively sensed (CS) measurements, our non-iterative algorithm is capable of high quality reconstructions. Notice how fine structures like tiger stripes or letter 'A' are recovered from only 4% measurements. Despite the expected degradation at measurement rate of 1%, the reconstructions retain rich semantic content in the image. For example, one can easily see that there are two tigers resting on rocks, although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
570
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 588 publications
(615 citation statements)
references
References 40 publications
(75 reference statements)
0
570
0
Order By: Relevance
“…Recently, another category of machine learning based SR approaches is developing quickly [17,18,19,20,21,22,23,24,25]. Machine learning has very good performance and applications on a variety of problems such as visual/speech recognition, natural language processing, and biomedical imaging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another category of machine learning based SR approaches is developing quickly [17,18,19,20,21,22,23,24,25]. Machine learning has very good performance and applications on a variety of problems such as visual/speech recognition, natural language processing, and biomedical imaging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, image reconstructions using total variation as regularizations could result in oversmoothed images with blurred boundaries between structures. Inspired by early work of using sparse dictionary learning‐based regularization for MR reconstruction, and more recent work of using convolutional neural networks (CNN) for natural image reconstruction, we propose to use a general CNN‐based regularization in this work. Specifically, assume MCNN:xartifactxclean maps an artifact‐contaminated image, mainly caused by k‐space undersampling and results in structural ghosting aliasing or incoherent noise‐like artifacts on image, to an artifact‐free image.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, assume MCNN:xartifactxclean maps an artifact‐contaminated image, mainly caused by k‐space undersampling and results in structural ghosting aliasing or incoherent noise‐like artifacts on image, to an artifact‐free image. It can be represented by multiple layers of convolutional kernels parameterized by θ . Hence, a compact representation of this mapping is:MCNNfalse(xitalicartifactx007C;θfalse)=xclean…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep neural network (DNN) architectures, convolutional neural network (CNN) in particular, are finding more and more applications in medical imaging analysis for various problems including classification, detection and segmentation . It has already been demonstrated that CNN outperforms sparsity‐based methods in super‐resolution reconstruction …”
Section: Introductionmentioning
confidence: 99%